Modern Approach to Treatment of Patients with Odontogenic Cyst of Jaw - Hushvakhtov, D.I.; Mirzoev, M.Sh.; Jonibekova, R.N.; Gafarov, Kh.O.; Schakirov, M.N. (KnE Materials Science, 2017)
Contrary to existing contraindication for cystectomy, we can conclude that extensive odontogenic cysts of jaw with involved of more than 2-3 intact teeth and with loss of lower bone wall for more than1 cmisn’t the only sign for cystotomy. Application of correctly selected bone and plastic materials (in our case nickelid titanium granules in combination with PBRP) contributes to restoration of large-scale bone defects with formation of organotypical bone, corresponding to anatomy of the part, in optimal period of time which shortens the postsurgical rehabilitation period of patients and contributes to early functional loading to organ.